COMPARATIVE EFFICACY OF SACUBITRIL/VALSARTAN VERSUS ACE INHIBITORS OR ARBS IN ACHIEVING TARGET BLOOD PRESSURE AMONG ADULTS WITH HYPERTENSION: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - DAS, PRANAB (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: To evaluate the comparative efficacy of sacubitril/valsartan versus angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) in achieving blood pressure (BP) control (<140/90 mmHg) among adults with hypertension. Methods: A meta-analysis was conducted following PRISMA 2020 guidelines. Randomized controlled trials (RCTs) comparing sacubitril/valsartan with ACEIs or ARBs in adult hypertensive patients and reporting the proportion of individuals achieving target BP were included. Four eligible RCTs were identified through systematic searches of PubMed, EMBASE, Cochrane CENTRAL, and ClinicalTrials.gov. Risk of bias was assessed using the Cochrane RoB 2.0 tool, and the certainty of evidence was evaluated using the GRADE approach. A random-effects model was employed to pool risk ratios (RRs) with 95% confidence intervals (CIs). Results: The pooled analysis demonstrated that sacubitril/valsartan was significantly more effective than ACEIs or ARBs in achieving BP control, with a pooled RR of 1.24 (95% CI: 1.14–1.35). Heterogeneity was moderate (I² = 58.2%), and leave-one-out sensitivity analyses confirmed the robustness of the results. No significant publication bias was detected through Egger’s regression or funnel plot inspection. The overall certainty of the evidence was rated as moderate. Conclusion: Sacubitril/valsartan improves the likelihood of achieving target blood pressure levels compared to ACEIs or ARBs in adults with hypertension. These findings support the potential of angiotensin receptor-neprilysin inhibitors (ARNIs) as a more effective therapeutic option in contemporary hypertension management.